Advances in Bioinformatics and Computational Biology 8th Brazilian Symposium on Bioinformatics, BSB 2013, Recife, Brazil, November 3-7, 2013, Proceedings - Setubal, João C.; Almeida, Nalvo F. (Lecture Notes in Bioinformatics, 2013)
This book constitutes the refereed proceedings of the 8th Brazilian Symposium on Bioinformatics, BSB 2013, held in Recife, Brazil, in November 2013. The 18 regular papers presented were carefully reviewed and selected for inclusion in this book. The papers cover all aspects of bioinformatics and computational biology.